Persistensi Herbisida Clomazone dan Pendimethalin pada Tanaman Kedelai Kultivar Argo Mulyo - Hasanuddin Hasanuddin; Elly Kesumawati; Jumini Jumini (Jurnal Agrista, 2008)
The Persistence of Clomazone and Pendimethalin Herbicides in Soybean Cultivar of Argo MulyoABSTRACT. A field research has been conducted in PT. Syngenta RD Station Cikampek, Karawang to investigate the persistence of clomazone and pendimethalin herbicides in soybean cultivar of Argo Mulyo. The dosage of clomazone and pendimethalin herbicides used were: 0.75; 1.50; and 2.25 kg a.i. ha-1. The persistence of clomazone and pendimethalin herbicide varied from 28 to 96 days and 43 to 75 days, respectively. The persistence of clomazone herbicide was longer than the of pendimethalin.